Synthetic polymer/single‐crystal composite1. (9th June 2014) - Liu, Yujing; Chen, Liao; Liu, Wei; Ye, Tao; Chen, Hongzheng; Li, Hanying; Lendlein, Andreas; Behl, Marc
<x xml:space="preserve">Abstract</x> Biogenic single‐crystals have been found to incorporate biomacromolecules and become biomacromolecule/single‐crystal composites. The complex composite structures and properties of these biogenic crystalline materials have spurred investigations to reproduce their synthetic analogs, polymer/single‐crystal composites. Here, we review recent progress of the synthetic polymer/single‐crystal composites, where the polymers are distributed inside the crystals in their aggregate states (micelles, particles, gel networks, and 3D structured forms). The mechanisms of the polymer incorporation are also discussed. Furthermore, the effects of the polymer incorporation on the properties of the crystal host are described. Copyright © 2014 John Wiley & Sons, Ltd.